2004
DOI: 10.1007/s00726-004-0114-4
|View full text |Cite
|
Sign up to set email alerts
|

The biological functions of polyamine oxidation products by amine oxidases: Perspectives of clinical applications

Abstract: The polyamines spermine, spermidine and putrescine are ubiquitous cell components. If they accumulate excessively within the cells, due either to very high extracellular concentrations or to deregulation of the systems which control polyamine homeostasis, they can induce toxic effects. These molecules are substrates of a class of enzymes that includes monoamine oxidases, diamine oxidases, polyamine oxidases and copper containing amine oxidases. Polyamine concentrations are high in growing tissues such as tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 80 publications
5
89
0
1
Order By: Relevance
“…In the MSA group, concentrations of N 1 -acetylcadaverine (P b 0.001), cadaverine (Pb 0.007), N 8 -acetylspermidine (Pb 0.005), total PAs (Pb 0.001), and putrescine spermidine -1 (Pb 0.05) were significantly increased, while concentrations of N 1 -acetylputrescine (Pb 0.001) and N 1 -acetylspermidine (Pb 0.001) were significantly reduced in the MSA group, as compared to the normal group (Table 1). It is interesting to note that the concentration of N 1 -acetylcadaverine is highly increased in the CSF of PD and MSA patients, and mainly metabolized by monoamine oxidase in mitochondria [17]. Dysfunctional mitochondria, a well-known cause of PD, can deregulate the concentration of N 1 -acetylcadaverine.…”
Section: Resultsmentioning
confidence: 99%
“…In the MSA group, concentrations of N 1 -acetylcadaverine (P b 0.001), cadaverine (Pb 0.007), N 8 -acetylspermidine (Pb 0.005), total PAs (Pb 0.001), and putrescine spermidine -1 (Pb 0.05) were significantly increased, while concentrations of N 1 -acetylputrescine (Pb 0.001) and N 1 -acetylspermidine (Pb 0.001) were significantly reduced in the MSA group, as compared to the normal group (Table 1). It is interesting to note that the concentration of N 1 -acetylcadaverine is highly increased in the CSF of PD and MSA patients, and mainly metabolized by monoamine oxidase in mitochondria [17]. Dysfunctional mitochondria, a well-known cause of PD, can deregulate the concentration of N 1 -acetylcadaverine.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, biogenic polyamine metabolism is one of the main targets of MGBG, which reduces the intracellular polyamine content through induction of spermidine-spermine acetyltransferase (SSAT) (involved in polyamine catabolism) (Regenass et al 1992) and inhibition of SAMDC (essential for polyamine synthesis) (Williams-Ashman and Schenone 1972). Again polyamine oxidation represents a crucial catabolic pathway in polyamine metabolism by which these polycations can be involved in oxidative stress and apoptosis (Agostinelli et al 2004). In this regard, it has been reported that MGBG is able to inhibit polyamine oxidase activity in thymus suggesting a positive role for this drug in HIV related diseases (Ferioli and Armanni 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular accumulation of polyamines, due either to high extracellular levels or deregulation of the systems that control polyamine homeostasis, can induce programmed cell death (or apoptosis) in various cell types (Tobias and Kahana 1995;Pignatti et al 2004;Seiler and Raul 2005). The natural polyamines spermidine and spermine are substrates of several enzymes that generate cytotoxic metabolites: monoamine oxidase (MAO), polyamine oxidase (PAO), spermine oxidase (SMO), and copper amine oxidases (CuAOs) Agostinelli et al 2004). Amine oxidases (AOs) are important because they regulate the levels of these polycations.…”
Section: Editorialmentioning
confidence: 99%
“…These toxic products are able to induce stress-activated signal transduction pathways, leading to cell death by necrosis or apoptosis (Lindsay and Wallace 1999;Seiler and Raul 2005;Agostinelli et al 2006b). These findings have a potential clinical application in cancer therapy Agostinelli et al 2004Agostinelli et al , 2010Averill-Bates et al 2008;Vijayanathan et al 2013;Amendola et al 2013). In light of this, a novel kind of super paramagnetic maghemite nanoparticles (SAMNs, surface active maghemite nanoparticles) were modified with BSAO, using rhodamine-isothiocyanate adduct as fluorescent spacer arm.…”
Section: Editorialmentioning
confidence: 99%